Answer:
x = - 4, x = 2
Step-by-step explanation:
Given
3x² + 6x - 24 = 0 ( divide through by 3 )
x² + 2x - 8 = 0 ← in standard form
(x + 4)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 4 = 0 ⇒ x = - 4
x - 2 = 0 ⇒ x = 2
Ok, to check back on what the measure of a radian is, it is 57.3 degrees. So it would be about .78
radians
Answer:
3) The function's leading coefficient is negative.
Explanation:
(1) Is not the answer because when x = 3, f(x) = 0.
(2) Is not the answer because when f(x) = -3,
x = 0.
(4) Is also not the answer because the y-values on both sides of (1, -4) are mirroring each other.
Therefore,
(3) is the answer, by elimination, but also because there is not proof of the leading coefficient being negative, as we don't see the original equation.
I hope this helped! :)
Caroline should have thought of what she wanted to do first. That way, it reduces Caroline's percentage.
Answer:
3x+2°=65° (vert opp angles)
3x=65°-2°
=63°
x=63÷3
=21